Pengaruh Brand Image, Harga, Brand Trust Dan Kualitas Produk Terhadap Keputusan Pembelian Lipstik Wardah Di Kota Semarang - Lestari, Meti; Wismantoro, Yohan (Politeknik Negeri Ambon, 2024)
In general, people really like the cosmetics industry, one of which is lip care which is growing rapidly in Indonesia. The aim of this research is to test the influence of brand image, price, brand trust and quality of Wardah lipstick products on purchasing decisions in the city of Semarang. This study uses a quantitative approach. Sample collection used a purposive sampling method with 175 respondents by distributing questionnaires using Google from. The data analysis process uses SMARTPLS. The results of data processing show that Brand Image and Brand Trust have a significant influence on the decision to purchase Wardah lipstick in the city of Semarang, while price and product quality do not have a significant influence on the decision to purchase Wardah lipstick in the city of Semarang. Keywords: Brand Image, Price, Brand Trust, Product Quality, Purchasing Decisions.